Optimization of a Vacuum Thermal Evaporation System for the Deposition of Bi–Sb–Te Thin Films - Omonov, Bunyodjon U.; Maxmudov, Sherzod A. (East European Journal of Physics, 2026)
In this study, thin films based on bismuth and antimony chalcogenides (Bi2Te3–Sb2Te3) were synthesized using an optimized thermal evaporation vacuum system, and their morphological characteristics were thoroughly investigated. Atomic force microscopy (AFM) results revealed nanoscale granularity on the film surface (in the range of 50–150 nm) and a distinct stepped morphology. Longitudinal profile analyses indicated that the height variations lie within the range of 0.790–0.798 μm. Scanning electron microscopy (SEM) observations confirmed the formation of grains, larger particles, and surface voids, indicating a dual-level morphological structure. Such a structure is critically important for enhancing thermoelectric efficiency by intensifying phonon scattering, thereby reducing thermal conductivity while preserving electron transport properties. The findings demonstrate that Bi2Te3–Sb2Te3-based thin films possess high scientific and practical potential as thermoelectric materials.